Melioidosis in Animals, Thailand, 2006–2010 - Direk Limmathurotsakul; Suree Thammasart; Nattachai Warrasuth; Patiporn Thapanagulsak; Anchalee Jatapai; Vanna Pengreungrojanachai; Suthatip Anun; Wacharee Joraka; Pacharee Thongkamkoon; Piangjai Saiyen; Surasakdi Wongratanacheewin; Nicholas P.J. Day; et al. (Emerging Infectious Diseases, 2012)
We retrospectively estimated the incidence of culture-proven melioidosis in animals in Thailand during 2006–2010. The highest incidence was in goats (1.63/100,000/year), followed by incidence in pigs and cattle. The estimated incidence of melioidosis in humans in a given region paralleled that of melioidosis in goats.